Articulating “Responsibility” as a Prerequisite for the Arab Spring (American Journal of Islam and Society, 2012)
In delineating the causes behind nonmilitant uprising and revolution in the Middle East, I propose that the import, the Arabization and Islamization of the term responsibility, as a key catalyst. Although the concept of responsibility is fundamental to the message of Islam, it is alluded to by an assortment of terms that seem to have fallen out of the day-to-day vernacular of Arab communities. The adoption of the term mas’uliyyah has served to express this fundamental concept. Furthermore, given its origin in post-Enlightenment Western political philosophy, the term provides a rare conceptual bridge between regions termed Western and Middle Eastern, in addition to being a linguistic vehicle capable of coarticulating modern Western and traditional Islamic thoughts. In this article, I trace the Arabization and Islamization of the term responsibility to nineteenth-century nahDah literature and its current establishment in different Islamic currents and schools. Moreover, I explain the utility of the term to express authentically Islamic vocabulary that has been forsaken in political terminology of the past two centuries.I propose that the presence of this now familiar term was instrumental in articulating the necessity of political change in a manner that resonated with millions of Arabs educated according to a modern Western model of education. Finally, I predict that the term responsibility will allow for a “new kinda fiqh” appropriate for an activated citizenry.